'Hardly a kent name absent': Raising Capital in Scotland via Tontine, 1775–1850. Issue 1 (May 2023) - McDiarmid, Andrew
Abstract : Scotland, unlike England and Ireland, was never the site of a state-operated tontine. Despite this, the scheme developed independently of the state, becoming popular with private groups as a means of raising funds for building works. Part life annuity and part lottery, this financial instrument was used to provide capital for a range of projects in Scotland, including hotels, coffeehouses, and assembly rooms. This article identifies successful and unsuccessful Scottish tontines between 1775 and 1850. It hypothesises that local private tontines were most successful when they operated a proto-Environmental, Sustainable and Governance (ESG) investment model. This is demonstrated by the aims driving successful tontines, in which investors were offered the opportunity to invest in projects that would make a tangible change to the local community and the lives of those in it. Unsuccessful tontines are meanwhile highlighted for failing because of one or more of the following factors: organisers attempted to raise too large a sum via subscriptions; their aims did not offer a tangible benefit to, or which was detached from, the local community and area; or those behind the scheme were from outwith the local community.